Opportunities and Challenges to Increase Inter- and Transdisciplinarity: A Qualitative Study of the FloodRISE Project - Julien Forbat (Journal of MultiDisciplinary Evaluation)
Background: The FloodRISE project, which started in 2013 in Southern California, aimed at better understanding how to promote resilience to coastal flooding. It was based on a cross-disciplinary approach, involving several research teams and local communities.